Best Practices for Social Work with Refugees and Immigrants - Potocky-Tripodi, Miriam; Naseh, Mitra (Columbia University Press, 2019)
The second edition of Best Practices for Social Work with Refugees and Immigrants offers an update to this comprehensive guide to social work with foreign-born clients and an evaluation of various helping strategies and their methodological strengths and weaknesses. It incorporates the latest research to provide a practical, up-to-date resource